ADAPTIVE STRATEGIES OF THE HALOPHYTE POPULATIONS - Glukhov, O. Z.; Kharkhota, G. I.; Prokhorova, S. I.; Agurova, I. V. (Annali di Botanica, 2013)
Studies of the adaptive strategies of halophytes at different levels of their organization are important not only for assessment of their health condition and prognosticating their future behaviors, but also for testing potential suitability of technogenic edaphotopes for plant growth without making additional analyses. We investigated the population structure and morphological variation of three halophilic Gypsophyla L. species which actively spread in different technogenic ecotopes of Ukraine by methods generally accepted in ecology and phytocenology. By the type of strategy populations of species of the genus Gypsophila in technogenic edaphotopes can change the primary type of strategy for the secondary, or gain the stress-tolerant type, mainly due to the changes of parameters of seed productivity. The studied populations are stable with predominance of individuals which reached the prereproductive and reproductive stages of their development. At the organism level the species differ by phenotypic plasticity revealing in compensatory development of vegetative and generative organs. This reflects not only in absolute values of parameters of features, but also when calculating the coefficients of divergence, variation, as well as the vitality classes in populations.By the adaptive strategy halophytes are candidates for use in local phytoremediation of disturbed lands.